Stimulatory Effect of Indole 3-Acetic Acid and Benzyladenin on Two Varieties of Antirrhinum Majus L. - J. Sidkey, Ban A. (Iraqi Journal of Science, 2023)
This research had been conducted to investigate response of two Antirrhinum majus L. varieties, tall and dwarf variety to foliar application of Indole 3-acetic acid and Benzyladenin at (0, 60, 120, 180, 240 ppm), through plant height, fresh weight, dry weight of shoot, length of inflorescence (raceme), number of flowering buds per raceme and chlorophyll content in leaves at complete flowering stage.Results of treatment of the tall variety with IAA and BA showed that IAA had the highest significant increase in plant height, while BA had the highest significant increase in chlorophyll content .Increasing concentrations of both IAA and BA resulted a significant increase in all growth parameters, this was obvious in flowering buds per raceme ,hence both IAA and BA treatment at 240 ppm was more significant than 180 ppm that was more significant than 120 ppm.Results of treatment of the dwarf variety with IAA and BA showed that there was a significant increase in number of flowering buds per raceme, hence the treatment with BA was more significant than IAA .Increasing concentrations of both IAA and BA increased all growth parameters except chlorophyll content in leaves, this was obvious in flowering buds per raceme ,hence both IAA and BA treatment at 240 ppm was more significant than 180 ppm that was more than 120 ppm